The Angiostrongylus vasorum Excretory/Secretory and Surface Proteome Contains Putative Modulators of the Host Coagulation - Germitsch, Nina; Kockmann, Tobias; Asmis, Lars M.; Tritten, Lucienne; Schnyder, Manuela (Frontiers in Cellular and Infection Microbiology, 2021)
Angiostrongylus vasorum is a cardiopulmonary nematode of canids and is, among others, associated with bleeding disorders in dogs. The pathogenesis of such coagulopathies remains unclear. We performed a deep proteomic characterization of sex specific A. vasorum excretory/secretory proteins (ESP) and of cuticular surface proteins, and evaluated the effect of ESP on host coagulation and fibrinolysis in vitro. Proteins were quantified by liquid chromatography coupled to mass spectrometry and functionally characterized through gene ontology and pathway enrichment analysis. In total, we identified 1069 ESP (944 from female and 959 from male specimens) and 1195 surface proteins (705 and 1135, respectively). Among these, we identified putative modulators of host coagulation, e.g., von Willebrand factor type D domain protein orthologues as well as several proteases, including serine type proteases, protease inhibitors and proteasome subunits. The effect of ESP on dog coagulation and fibrinolysis was evaluated on canine endothelial cells and by rotational thromboelastometry (ROTEM). After stimulation with ESP, tissue factor and serpin E1 transcript expression increased. ROTEM revealed minimal interaction of ESP with dog blood and did not influence the onset of fibrinolysis. We thus conclude that Angiostrongylus vasorum ESP and surface proteins are not solely responsible for bleeding in dogs. The interaction with the host’s vascular hemostasis is limited. It is likely that coagulopathies in A. vasorum infected dogs are the result of a multifactorial response of the host to this parasitic infection.